Use of natural compounds for obtaining and projecting a product for the treatment of confined agricultural and livestock waste (Research, Society and Development, 2020)
The present research had as general objective to elaborate an experimental design that allowed to formulate a product based on natural compounds that acted efficiently in the treatment of bovine urine (pH control and odor minimization), developed were then corroborated to computational tools. The results showed that 47 drops of Tahiti lemon were necessary for the neutralization of 50 mL of urine, being necessary the use of three drops of the lemongrass essence for the minimization of the odor. The theoretical calculations showed how the interactions of citric acid with urea and uric acid occur, evidencing that citric acid interacts with approximately the same intensity with both urea and uric acid, justifying the experimental results found.